2014
DOI: 10.1089/gtmb.2013.0407
|View full text |Cite
|
Sign up to set email alerts
|

ABCB1 C3435T Polymorphism and the Risk of Coronary Heart Disease: A Meta-Analysis

Abstract: The current meta-analysis suggests that ABCB1 C3435T polymorphism may contribute to the risk of CHD, especially for MI and ACS, among Caucasian populations. Thus, detection of ABCB1 C3435T polymorphism may be a promising biomarker for the early detection of CHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…ABCB1’ s promoter region contains multiple transcription factor binding sequences, including specific protein 1, activator protein 1, nuclear factor interleukin (IL) 6, and forehead transcription factor or T cell factor/lymphoid enhancer factor, suggesting the presence of a complex regulatory mechanism [ 18 ]. A previous study has shown that certain specific polymorphisms in the promoter region of ABCB1 may play an important regulatory role in coronary heart disease occurrence and development [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ABCB1’ s promoter region contains multiple transcription factor binding sequences, including specific protein 1, activator protein 1, nuclear factor interleukin (IL) 6, and forehead transcription factor or T cell factor/lymphoid enhancer factor, suggesting the presence of a complex regulatory mechanism [ 18 ]. A previous study has shown that certain specific polymorphisms in the promoter region of ABCB1 may play an important regulatory role in coronary heart disease occurrence and development [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…ABCB1 has been reported to mediate the process of systemic inflammation [ 19 ]. On the one hand, ABCB1 can secrete endogenous inflammatory mediators, such as prostaglandins and leukotrienes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation